2010
DOI: 10.1542/peds.2009-2869
|View full text |Cite
|
Sign up to set email alerts
|

Late Preterm Infants: Birth Outcomes and Health Care Utilization in the First Year

Abstract: LPIs are at increased risk of poor health-related outcomes during their birth hospitalization and of increased health care utilization during their first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 52 publications
5
84
0
14
Order By: Relevance
“…The implication that late-preterm children have a propensity for more-severe illness is consistent with the results of previous studies that demonstrated higher rehospitalization rates and higher hospital costs for late-preterm infants, compared with term infants, in the first year of life. 12,13 Our findings also suggest that lownormal gestational ages of 37 to 38 weeks might confer increased risk of early childhood asthma, compared with gestational ages of Ն39 weeks, as suggested in other studies. 25,26 This association is noteworthy, given recent epidemiological trends in gestational length for US births.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The implication that late-preterm children have a propensity for more-severe illness is consistent with the results of previous studies that demonstrated higher rehospitalization rates and higher hospital costs for late-preterm infants, compared with term infants, in the first year of life. 12,13 Our findings also suggest that lownormal gestational ages of 37 to 38 weeks might confer increased risk of early childhood asthma, compared with gestational ages of Ն39 weeks, as suggested in other studies. 25,26 This association is noteworthy, given recent epidemiological trends in gestational length for US births.…”
Section: Discussionsupporting
confidence: 84%
“…[2][3][4][5][6][7][8][9][10][11] Furthermore, there is evidence that, in the first year of life, late-preterm infants have a propensity for more severe illnesses and might require more medical services when hospitalized. [12][13][14] To date, however, the full magnitude of potential long-term morbidities for this population and their public health impact have not been well studied. The Eunice Kennedy Shriver National Institute of Child Health and Human Development has identified the economic impact and long-term health impact of late prematurity as priority areas of research.…”
mentioning
confidence: 99%
“…This is specifically true for preterm infants that spend weeks in separation. It has been shown that there is a poor quality of survival with respect to their immunity (Baron et al 2011;Bird et al 2010), IQ and scholastic achievement (Jain 2008;Morse et al 2009). SSC with Zero Separation is the biological normal (default) and is the one intervention above any other that can improve quality of survival.…”
Section: The Case For Zero Separationmentioning
confidence: 99%
“…6 Preterm birth carries even greater short-term and long-term morbidity. [7][8][9] Worldwide, preterm birth is increasing and this increase, in some populations, has been attributed to planned preterm birth. 10 Whether increased planned early birth rates have led to any increases in neonatal morbidity or reductions in stillbirth rates, and the extent to which implementation of restrictions on planned birth before 39 weeks could affect stillbirth rates, is uncertain.…”
Section: Introductionmentioning
confidence: 99%